INOVASI SAMPAH RUMAH TANGGA MENJADI PUPUK CAIR DI KOMPLEKS POLRI HAJIMENA - Yuli Ambarwati; Syaiful Bahri; Sri Waluyo; Yessi Mulyani; Eksa Ayumi; Putri Syahwa Rahman (Jurnal Abdi Insani, 2026)
The increasing volume of household waste in the Hajimena Police Complex, South Lampung, Indonesia, which exceeds local processing capacity, has led to waste accumulation at final disposal sites (TPA) and poses a serious environmental challenge. This situation necessitates sustainable management efforts to prevent negative impacts on public health. An environmentally friendly approach that transforms waste into economically valuable products offers a promising solution. This community service program aimed to process household organic waste into liquid fertilizer using a simple solid-liquid (SL) technique that can be easily applied by residents. Organic waste such as food scraps, vegetables, and fruits was collected from households and processed using the SL method. The program also included socialization and hands-on training to enable residents to independently produce liquid fertilizer. The activity successfully improved community awareness and skills in managing organic waste. A total of 30 participants joined the training, which combined theoretical and practical sessions. Evaluation results showed a significant improvement in participants’ understanding, with average scores increasing from 56.8% (pre-test) to 85.5% (post-test). Participants demonstrated strong enthusiasm to apply the technique independently. In conclusion, this community service program effectively enhanced the community’s knowledge and awareness of sustainable organic waste management in the Hajimena Police Complex.